Relationship between Remittance and Economic Growth: Evidence from Bangladesh - Sarkar, Md. Sujahangir Kabir; Rahman, Md. Zillur; Islam, Mohammad Muzahidul; Sikdar, Md. Mehedi Hasan; Khan, Abul Basher (American Journal of Trade and Policy, 2018)
Remittance is one of the major sources of capital especially for the developing countries like Bangladesh. This study attempts to explore the relationship between remittance and economic growth in Bangladesh. Time series data from 1995-2016 extracted from the World Bank database as well as Bangladesh Bank statistics were used to measure the relationship of remittance and gross domestic product (GDP) with some other variables such as gross capital formation, gross domestic saving and household final consumption expenditure. Pearson’s correlation coefficient is estimated between the variables. Moreover, annual growth (%) of remittance earning by Bangladesh has been calculated and compared with the GDP growth of Bangladesh. The study has found that on an average, remittance of Bangladesh has been increased by 10.85% from 1995-2016 which is higher than the average growth of the country’s GDP. It has revealed that there is a positive relationship of remittance with the GDP, gross capital formation, domestic saving and household final consumption expenditure in case of Bangladesh. However, there is a frequent fluctuation of remittance flow in Bangladesh in the recent years. Thus, this study recommends that Bangladesh should take proper initiatives for maintaining an increasing trend of remittance in the coming years which would be useful for the socio-economic development of the country.